PERAN GEREJA DALAM PELAYANAN PASTORAL TERHADAP PASANGAN HAMIL SEBELUM MENIKAH - Jonidius Illu (Phronesis: Jurnal Teologi dan Misi, 2020)
One focus of church service is to prepare Christian families who live righteously through premarital counseling.Marriage is prepared for a lifetime.One of the efforts of the church in realizing church members who live holy lives is by giving teachings about love and choosing a partner according to the Bible so that church members do not commit adultery and sexual intercours outside of marriage which results in pregnancy outside of marriage. This study aims to understand marriage and build a Christian family that is in accordance with the Bible and provide understanding that having sexual relation not within the container of Christian marriage is adultery so that both men and women need to confess their sins before God. It was concluded that the Church is responsible for providing pastoral care to couples who become pregnant out of wedlock.The church in carrying out the principle of love still observes the rules so that the maturity of the church members become realized.